Peripheral PD-1+ T Cells Co-expressing Inhibitory Receptors Predict SVR With Ultra Short Duration DAA Therapy in HCV Infection - Romani, Sara; Stafford, Kristen; Nelson, Amy; Bagchi, Shashwatee; Kottilil, Shyam; Poonia, Bhawna (Frontiers in Immunology, 2019)
Direct acting antiviral (DAA) regimens of 12 weeks result in HCV clearance in vast majority of patients across genotypes. We previously demonstrated an ultra-short regimen of 4 weeks DAA cleared HCV in a subset of patients. Here, we hypothesized that individual level of antiviral immunity differentially influenced viral clearance and investigated biomarkers of a successful response. Cohorts of HCV patients treated for 4 weeks with DAA therapy who either achieved sustained virologic response (SVR) or relapsed were compared at baseline and at end of therapy (EOT) for immune cell phenotypes and HCV specific immunity. Higher levels of PD-1+ CD8+ and CD4+ T lymphocytes co-expressing inhibitory receptors (IR) were present at baseline and at EOT in HCV patients who eventually achieved SVR compared with those who relpased. HCV specific CD8+ T cells were predominantly contained within these IR expressing PD-1+ subsets. Patients in the SVR group had significantly higher CD8+ T cell degranulation in response to HCV peptides at baseline and higher levels of cytokine producing T cells at EOT time-point, relative to those who relapsed. In ex vivo cultures, PD-1+CD160+ CD8+ T cells had higher HCV specific degranulation and PD-1+2B4+ CD8+ T cells had higher cytokine expression (IFNγ+TNFα+ or IFNγ+CD107a+) compared with single or no IR expressing subsets, indicating higher virus specific functional capacity of these subsets. Receiver operating characteristics curve (ROC) for baseline circulating frequencies of PD-1+CD160+, PD-1+Tim-3+ CD8+ T cells and PD-1+CD160+, PD-1+Blimp-1+, PD-1−CTLA4+ CD4+ T cells respectively, had associated C-statistics of 0.8214 and 0.9451 for discriminatin of patients who successfully cleared HCV with 4 weeks treatment. Thus, PD-1+ virus-specific CD8+ T cell subsets with cytotoxic capacity are present in a subset of chronic HCV infected individuals that associate with ability to achieve SVR, indicating role of immunity in DAA mediated viral clearance with short duration therapy.